POLA DISTRIBUSI KAYU PENGHARA UNTUK INDUSTRI PENGGERGAJIAN DI DAERAH JAWA TIMUR - Subandi Antaatmadja; Rachman Effendi (Jurnal Penelitian Hasil Hutan, 1989)
Logs  as raw  material  of  sawmilling  industry   in East Java are provided   by  Forest  District  Administration    of  Perum Perhutani.   Every   year  Perum   Perhutani   makes   a  plan   to  distribute    the  raw  material  for  sawmilling   industry.   Perum  Perhutani,    in  particular   Unit   Two   East  Java,    has  been  striving  for  improving   the  raw  material  supplies   throught   the improvement    of  quality  of  teak  logs continuity    of  supply.In determining  the distribution   pattem   of  raw materials from  forest  districts  to individual  sawmill  transportation   cost  should   be  one  of  deciding  factors.The  aim  of  this  investegation   is  to  find   the  distribution   pattern  of  transporting   the  logs from  forest  districts   to  individual  sawmill so as to minimize   the  total  transportation   cost.  The results  of  the investigation  are :1.Jatirogo sawmill  is the largest supplier  of logs while Gresik is the smallest. 2.The minimum   total cost  of  transporting  the raw material  is Rp 229.314.150,-.